Yuri Temirkanov conducts Prokofiev with Denis Matsuev Annecy Classic Festival - Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953 (Idéale Audience, 2015)
The program for the Annecy Classic Festival focuses on the work of Prokofiev. Led by Yuri Temirkanov, the Saint Petersburg Philharmonic Orchestra, alongside Denis Matsuev on the piano, delivers a brilliant performance of the composer's piano Concerto No. 3. This is the most popular of Prokofiev's piano concertos. In his words, the audience "barely understood it, but they supported it all the same." The themes are borrowed from Russian folk tunes to which the composer added speed and virtuosity. Composed in 1935, Romeo and Juliet was Prokofiev's first great ballet of the Soviet period. Performed as part of a sequence, this composition reinforces the exceptional thematic richness. Despite its fundamentally classic tone, the work shows a certain harmonic violence that as a forbearer to his futuristic and expressionist works
Keywords: Concertos (Piano); Ballets; Ballets -- Excerpts; Webcast; Internet videos; Vidéos sur Internet